Relations between results on Raven Progressive Matrices Plus sets and school achievement - Matešić, Krunoslav (Array, 2000)
The relationships between results on the SPM+ and school grades were analysed for nine school subjects, including indicators of average school performance on a sample of 437 high school students. Correlation coefficients between SPM+ and final school achievement vary in range from 0.14 (history) to 0.35 (physics). The results do not support the hypothesis that teachers penalize intelligent students by giving them lower makrs at the half-term in order to encourage them to work harder.